Description of Paralactobacillus selangorensis gen. nov., sp. nov., a new lactic acid bacterium isolated from chili bo, a Malaysian food ingredient - Leisner, J J; Vancanneyt, M; Goris, J; Christensen, H; Rusul, G (Microbiology Society, 2000)
Paralactobacillus selangorensis gen. nov., sp. nov. is described. This organism, isolated from a Malaysian food ingredient called chili bo, is an obligatory homofermentative, rod-shaped lactic acid bacterium. The G+C content is 46.1-46.2±0.3 mol%. Earlier 16S rRNA studies showed that this organism constitutes a new taxon distantly related to the Lactobacillus casei-Pediococcus group. A phenotypic description that distinguishes Paralactobacillus selangorensis from other genera of lactic acid bacteria is presented. The type strain of Paralactobacillus selangorensis is LMG 17710(T).